2015
DOI: 10.1177/089875641503200103
|View full text |Cite
|
Sign up to set email alerts
|

Suspect Odontogenic Infection Etiology for Canine Lymphoplasmacytic Rhinitis

Abstract: The role of odontogenic infection as an etiology for lymphoplasmacytic rhinitis in dogs was evaluated. An association between odontogenic infection and inflammatory rhinitis was identified in 55% of cases evaluated. Odontogenic infection was unlikely or undetermined in 10% and 35% of the cases, respectively. Cases of lymphoplasmacytic rhinitis had roentgen signs associated with endodontic disease, periodontal disease, or retained tooth roots in 60%, 45%, and 25% of the cases, respectively. A collaborative team… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 65 publications
2
24
0
3
Order By: Relevance
“…1) Eosinophile und lymphoplasmazelluläre Entzündungen der Schleimhaut waren auch bei anderen Primärerkrankungen nachweisbar. Gerade lymphoplasmazelluläre Entzündungen ließen sich häufiger bei Patienten mit OND als bei Hunden mit IR nachweisen [13]. 2) Bei Hunden mit einer IR und Nachweis einer eosinophilen oder lymphoplasmazellulären Rhinitis, bei denen Tasker et al [3] aufgrund des Zellbilds von einer allergischen Komponente ausgehen würden, konnte auch bei entsprechender Therapie, wie z.…”
Section: Hunde Mit Idiopathischer Chronischer Rhiniɵs N=17unclassified
“…1) Eosinophile und lymphoplasmazelluläre Entzündungen der Schleimhaut waren auch bei anderen Primärerkrankungen nachweisbar. Gerade lymphoplasmazelluläre Entzündungen ließen sich häufiger bei Patienten mit OND als bei Hunden mit IR nachweisen [13]. 2) Bei Hunden mit einer IR und Nachweis einer eosinophilen oder lymphoplasmazellulären Rhinitis, bei denen Tasker et al [3] aufgrund des Zellbilds von einer allergischen Komponente ausgehen würden, konnte auch bei entsprechender Therapie, wie z.…”
Section: Hunde Mit Idiopathischer Chronischer Rhiniɵs N=17unclassified
“…In addition, Peeters et al demonstrated that cytokine and chemokine expression profiles in SNA and LPR differ, implying two different disease entities [ 15 ]. Odontogenic infections could also be implicated in LPR [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies revealed that innate immunity and hypersensitivity could be implicated in the pathogenesis of LPR [ 1 – 3 , 8 , 11 , 12 ]. Odontogenic infections could also be involved in LPR [ 13 ]. According to some studies LPR is a complex disorder that could arise in consequence of bacterial and fungal infections [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Die Ursache der idiopathischen Rhinitis ist bis heute nicht geklärt [14,18,21,22]. Sie stellt eine Ausschlussdiagnose (CT und Endoskopie!)…”
Section: Idiopathische Rhinitisunclassified
“…die nasale Mukosa gereizt und es kommt zu einer Rhinitis[14]. Durch oronasale Defekte gelangen Wasser und/oder Futter in die Nasenhöhle und fördern eine inflammatorische Reaktion der Nasenschleimhaut[15].…”
unclassified